Design and development of multi-lane smart electromechanical actuators - Annaz, Fawaz Yahya (The Institution of Engineering and Technology, 2014)
The book is divided into 7 chapters covering: relevant developments; modelling the brushless dc motor; control design; architecture consolidation; hardware cross monitoring;and digital cross monitoring. Appendices on hardware cross monitoring and digital cross monitoring are given.